Pengaruh Inflasi, Kurs, dan BI 7-Day Rate terhadap Indeks Saham Syariah Indonesia (ISSI) Periode 2015-2020 - Saputra, Susilo Adi; Gloria, Chenny Maulyca; Asnaini, Asnaini (IAIN Kudus, 2021)
The purpose of this study is to analyze the effect of inflation, exchange rates, and bi-7-day ratios on the Indonesian Sharia Stock Index (ISSI) for the 2015-2020 period. The method used in this research is to collect data such as through website and library studies. Data analysis in this study uses multiple ECM analysis with the help of the Eviews 8 computer program. The results of this analysis indicate that the inflation variable has an influence on the Indonesian Islamic stock index. However, the exchange rate and the bi 7 day rate do not have a significant effect on the Indonesian Islamic stock index.